PENGARUH CASH RATIO, DEBT TO EQUIT RATIO DAN NET PROFIT MARGIN TERHADAP EARNING PER SHARE PADA PT. NIPPON INDOSARI CORPINDO Tbk PERIODE 2012-2023 - Rizki Oktari, Adinda; Sairin (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of Cash Ratio, Debt to Equity Ratio and Net Profit Margin on Earning Per Share at PT Nippon Indosari Corpindo Tbk for the period 2012 - 2023. The research method used is a descriptive method with a quantitative approach. The population in this research is the financial report of PT Nippon Indosari Corpindo Tbk. The method used in this research is multiple regression analysis, classical assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. Significant tests include the t statistical test and the f statistical test, as well as coefficient of determination. The data was processed and analyzed using the SPSS version 26 program. The results of this research show that the Partial Cash ratio   has a significant negative effect on Earning Per Share, with a significant value of 0.005. Partially, Debt to Equity Ratio has a significant effect on Earning Per Share, with a significant value of 0.004. Partially, Net Profit Margin has a significant effect on Earning Per Share, with a significant value of 0.024. Simultaneously Cash Ratio, Debt to Equity Ratio and Net Profit Margin have a significant effect on Earning Per Share.